DAMPAK PENGAWASAN DAN MOTIVASI TERHADAP DISIPLIN BELAJAR MAHASISWA - Katim, Katim (Economic Faculty, Attahiriyah Islamic University, 2018)
The purpose of this paper is to examine the effect of supervision and motivation on discipline. Survey methodology was used to obtain self-report data from a sample of 90 students in courses at a public university. Results revealed that supervision and motivation have a positive correlation with discipline. Indicates that the more effective supervision and motivation, the higher the student's discipline will be. Implications and suggestions are discussed in the paper. Keywords: supervision, motivation, discipline